Homelessness and mental health. Issue 2 (March 2015) - Perry, Jennifer; Craig, Tom K.J.
<x xml:space="preserve">Abstract</x> The prevalence of serious mental illness is higher in homeless people compared with those who are housed, and there are higher rates of personality disorder, self‐harm and attempted suicide. In this article, the authors discuss interventions in primary and secondary care that focus on improving the mental health of homeless people